The effect of ball versus locator attachment system on the performance of implant supported overdenture: A systematic review - Nimmi Gupta; Rajesh Bansal; Neeteesh K. Shukla (Journal of Oral Biology and Craniofacial Research)
Objective: This systematic review was aimed to compare ball and locator attachment system on the basis of clinical and biomechanical performance of implant supported overdenture as well as biological and patient related outcomes. Material and methods: Open and free electronic and manual searches were performed in digital databases including MEDLINE via PubMed, the Cochrane Database of Clinical Trials, and Scopus along with some other reliable sources. From the 667 retrieved records, 11 full-text controlled trials were included in this study. Risk of bias was assessed according to RoB 2.0 except for one RCT (economic evaluation), only assessed by CASP checklist. Results: From the 11 retrieved studies, total 183 locator and 219 ball attachments were identified in 452 subjects of 30 yrs–95 yrs of age. Studies provided data about prosthodontic complications or maintenance (replacement or the activation of matrix and patrix part, loss of retention, fracture and relining of the prosthesis, fracture of the attachment and the survival probability), oral health impact profile, soft tissue parameters and periodontal complications, marginal bone loss, patient related outcome and cost of the attachment systems. Only 5 studies were assessed at low risk bias, while other 6 at moderate to high risk of bias. Conclusion: Locator attachment system show lesser complications including loss of retention and lower maintenance appointments, lesser soft tissue, and periodontal complications than the ball attachment. Ball is better in terms of cost effectiveness. In other related outcomes, no significant differences were noted between ball and locator attachment.